D-Dimer Serum Level Association With Mortality In Acute Stroke Patiens With Covid-19 - Moch Syahrial Pramudia Tarmidi; Nurul Fitria; Oryzasativa Giovanni; Akhdan Zharfan Puspito; Sintia Wahyu Arifah; Gibran Maulana Akbar (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2024)
Background: Since WHO declared COVID-19 a pandemic, Indonesia, including RSUD Gambiran Kediri, has experienced a sharp increase in morbidity and mortality. The global incidence of acute stroke in COVID-19 patients is 1.4%, with symptoms varying from mild to severe, including death. Elevated serum D-dimer in COVID-19 patients can be a biomarker to predict severe complications. Objective: This study aims to determine the relationship between elevated serum D-dimer levels (mild, moderate, severe) with mortality in acute stroke patients with COVID-19. Methods: Observational analytic study with a cross-sectional method using secondary data from medical records of patients admitted to RSUD Gambiran Kediri from March 2020 to June 2023. Patients were categorized based on serum D-dimer levels: normal (<0.5 mg/L), mild (<1 mg/L), moderate (1-2 mg/L), and severe (>2 mg/L). Results: Of 101 acute stroke patients with COVID-19, 52.48% were male. A total of 90 patients had elevated D-dimer levels, with 44 patients dying. Spearman correlation test and Chi-square test showed no significant association between D-dimer levels and mortality (p>0.005). Conclusion: There is no association between elevated serum D-dimer levels and mortality in acute stroke patients with COVID-19.